CHARACTERISTIC OF LINGUISTIC LANDSCAPE: A CASE STUDY OF HIGH EDUCATION SCHOOL IN TANJUNGPINANG - Abdu Rahmansah; Abrar Octavirandra Anjaru; Ayattullah Muhaddis Azim; Eki Pauziansah; Muhammad Arsy; Timoti Meilando; Nana Raihana Askurny (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Landscape linguistics is a part of sociolinguistics that discusses how language is used and displayed in public places, and how it can indicate cultural identity, power relations, and communication purposes. This study aims to identify the linguistic characteristics found on boards and signs in the higher school environment in Tanjungpinang, and Tanjungpinang is known to have a strong Malay culture. The focus of this research includes language and phrase structure, layout and communication function of the linguistic signs found. This research uses qualitative description method with data collection techniques in the form of observation, documentation and note-taking. Documentation is done by taking photos as the main tool, then further analyzed based on language version (monolingual, bilingual, and multilingual). The results showed that most of the advertisements were bilingual, namely with Indonesian - English and on the intitution signage it showed that most were bilingual by using Indonesian = Malay. This study concludes that the linguistic landscape in the high school environment in Tanjungpinang reflects the existence of multilingualism and identity representation in the educational public space at the high school in Tanjungpinang.